Studies on the emulsion scouring of raw wool - Grové, Christo Carel (Rhodes University, Faculty of Science, Department of Chemistry, 1963)
Knowledge of the mechanism of detergency under various conditions has thus far been built up from laboratory studies. It is well known that the laboratory methods for determing detergency are on the whole not able to give results which agree with those obtained in practice, probably because the actual scouring conditions cannot be duplicated exactly in the laboratory. Detergency testing on a full industrial scale is virtually impossible in view of the high cost and the production losses involved. In commercial raw wool scouring, which is an extremely complex system, it would be very difficult to exercise proper and complete control. The study described here was carried out on a specially constructed pilot plant which is similar to a fullscale plant in that the lengths of the bowls are of the same order as those of industrial plants, but they are considerably narrower. The trials were carried out under strictly controlled conditions in which the effects to be studied were created by the necessary changes while all other factors were kept constant, The pilot plant experiments were planned from indications of laboratory studies and the results were expected to be more comparable with those obtained in industrial practice, The effect of several factors on the scouring of raw wool was studied from the detergent efficiency aspect. The factors investigated were: mechanical action, backflow, temperature and detergency builders. A number of detergents which were selected from the large range which is available were compared with regard to efficiency and economy of scouring. A difficulty which hinders quantitative laboratory work on nonionic detergents is the fact that there is no rapid, accurate method for the estimation of nonionic detergents. The analytical methods which are employed at present are interfered with by virtually all the impurities which are normally present in scouring liquors. Some of the existing methods have been investigated and tested for precision and reproducibility and an attempt was made at establishing a new method. The sorption of nonionic detergents by various substrates has not been fully investigated because of the above reason and also because the amounts of detergent sorbed by most substrates are very small and difficult to determine. Attempts were made at determining the sorption of nonionic detergents onto wool and impurities which are normally found in scouring liquors. A new method for the investigation of "inactivation" of detergent by contaminants present in scouring liquors, which may be regarded as an indirect indication of detergent sorption, was investigated.
Keywords: Woolen and worsted manufacture